Causal effects of retinol and vitamin D on tongue cancer risk: a mendelian randomization study - Jiawei Zhang; Yake Lou; Hong Chen; Xiaofeng Huang (BMC Oral Health)
Abstract Background Previous studies have indicated that retinol and vitamin D may be associated with the oncogenesis of tongue cancer. Therefore, we aimed to assess the causal relationships of retinol and vitamin D with the risk of tongue cancer using the two-sample Mendelian randomization (MR) method. Methods Single nucleotide polymorphisms (SNPs) related to retinol, vitamin D and tongue cancer were obtained from the up-to-date genome-wide association study (GWAS) catalogue, which was screened for instrumental variables (IVs). We performed two-sample MR analyses and used inverse-variance weighted (IVW) as the primary method. Additionally, we used the MR-pleiotropy residual sum and outlier (MR-PRESSO) method, MR-Egger intercept analysis, Cochran’s Q test and leave-one-out analysis to evaluate the sensitivity of MR. Results The IVW method revealed that retinol was not significantly correlated with the risk of tongue cancer (OR = 0.8602; 95% CI = 0.4453–1.6617; P = 0.654). However, the causal relationship between vitamin D and the risk of tongue cancer was significant according to IVW (OR = 0.4003; 95% CI = 0.1868–0.8577; P = 0.019). The sensitivity analysis did not detect any significant horizontal pleiotropy or heterogeneity. Conclusions Given the limitations of this study, our MR study suggests that retinol is unlikely to influence the risk of tongue cancer, but vitamin D may decrease the risk of tongue cancer.